Analisis Hubungan Sipil-Militer terhadap Perubahan Kebijakan Pertahanan Jepang di Tahun 2015 - Fadilah, Edta Muhammad; Sudirman, Arfin (Jurnal Hubungan Internasional, 2018)
The change in defense policy that occurred during Shinzo Abe's reign in 2015 produced many pros and cons among the public. As a decision, it was not popular among civilians, either political elites or the public sphere because the administration made it in a hurry. Moreover, Japanese country was famous as a country with pacifism value after the Second World War. Therefore, the question arises as of why the decision was taken. This study uses the theory of Civil-Military Relations from Samuel Huntington to see whether there is a motive from the military to involve in the decision. Besides, this study also discusses military defense and professionalism of management in Japan to further illustrate the existence of military influence in the defense policy-making process and the political orientation of the Japanese military. The method used in this study is a qualitative research method. The author concludes that there was no interference by the Japanese army on the Japanese defense policy changes in 2015, but there was a scourge of civil-military relations in Japan which was initially a subjective civilian control into an objective civilÂian control.